Effects of Climate on Sandflies and Leishmaniasis in Endemic Areas of Bangladesh - Rahman, Md Fashiur; Banu, Selina; Alam, Md Jahangir; Uddin, Md Jalal; Sarker, Md Abu Sayeed; Sanjoba, Chizu; Shamimara, Mosammat; Hossain, Mohammad Mosharraf; Alim, Md Abdul; Matsumoto, Yoshitsugu; Rahman, Md Bahanur (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Climate includes rainfall, temperature; humidity has shown significant influences on Leishmaniasis and development of sand flies. Kala-azar- a climate-sensitive disease, a public health problem and historically endemic in Bangladesh, nurtured in temperatures ranging from 7 to 37°C, with relative humidity above 70%. Longevity and survival of vector of Kala-azar has been geographically controlled by the climate which is hard to manoeuver. Objective:To observe the relationship of climate and its effects on the development of sand flies and Leishmaniasis (Kala-azar) in the endemic areas in Bangladesh. Materials and Methods: This cross sectional study was conducted at the endemic areas of, Bangladesh during the period of 2014-2017. Information on climate like rainfall, humidity and temperature were collected from local respective Upazilla Live Stock Office and Bangladesh Meteorological Department, Agargaon, Dhaka. Month wise data of Kala-azar cases were collected from Directorate General of Health Services. Results: Temperature, Rainfall and Humidity are important for survivability and activity of sandfly as well asleishmaniasis. Mean temp at the study areas was found at around 20℃ in the month of Jan, Feb and Nov, Dec. Round the year the Maximum and Minimum temp was maintained at neither to high nor to low (between 7 to 36.5℃). Annual average humidity of these study area was found over 70%. In the study areas maximum rainfall 300to 500 mm was from May to Sep where peak was in Jun to Sep. Annual average rainfall was recorded 1434 to 1584 mm at Pabna and 2084 to 2182 mm at Mymensingh. Study findings correlated that rainfall may or may not have effects with sand fly and leishmaniasis. This study depicted distinct peaks of Leishmaniasis seen in pre monsoon Feb, monsoon Sep and post monsoon Nov period which dictated the plethora of sand fly from Jun to Oct and also from Jan to Feb. Conclusion: Manoeuvring the climate is difficult and it does not change each year, it will play its own role. We can manoeuver the harbour and the vector of leishmaniasis.Within this climatic condition National Kala-azar Elimination Programme has been fighting since 2008 but Kala-azar has not come to Zero. Further resurgence can it be outweigh? Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 10-14